The Effect of Gamification in Board Game to Improve Students’ English Vocabulary - Syahfrina Rahmawati; Vidya Mandarani; Fika Megawati (UNIB Press, 2023)
This study aims to determine whether there is a difference between the learning outcomes of English vocabulary improvement in descriptive text learning for students before and after the Gamification method is applied. The subjects of this study were 41 students of MTS Muhammadiyah 1 Taman. Data collection using tests in the form of multiple choice and essay to measure learning outcomes in English vocabulary improvement. The method used is quantitative method, data analysis using paired sample t test. The results show that the mean score of the post-test is higher than the mean score of the pre-test, this means that there is an increase in learning outcomes of English vocabulary after the Gamification method is applied, the results also show that the significance obtained is 0.000, which is smaller than 0.05, thus Ho is rejected and Ha is accepted. This means that there is a significant difference between the learning outcomes of English vocabulary in descriptive text learning before and after the implementation of learning strategies using the Gamification method.